PERUBAHAN SISTEM WARNA MENJADI WANGSA, LABELING KASTA PADA MASYARAKAT BALI - I Gusti Ketut Widana; I Gede Widya Suksma (WIDYANATYA, 2021)
At least there are some ties that make Balinese people's lives strongly bound, such as the "Color" system, which later developed into "Wangsa", which apparently cannot be separated from "Soroh", a kind of grouping of people based on blood relations by following the "Purusa" lineage vertically. In subsequent developments, the existence of "Color, House, and Soroh" is often identified, even explicitly mentioned as a form of "Casta", moreover it is also equipped with the appendages of "titles/titles" for each along with a hierarchical structure that is so well known and recognized. accepted as it is in the midst of Balinese society who incidentally is Hindu. This change in the Color system to Wangsa then became a kind of labeling the existence of a caste system in Balinese society.